The Effect of Procedural Justice on Managerial Performance Through Budget Participation at Pt. Perkebunan Nusantara (PERSERO) in North Sumatera - Wardani Harahap, L (KnE Social Sciences, 2018)
The budget participation is a budget arranged by involving the center manager responsibility. The role of the center manager responsibility is very closely related with the justice procedural because if all the center manager responsibility have taken part in conducting its duty and responsibility effectively and efficiently, thus will have conducted a fair procedure. This descriptive research approach is aimed to obtain an empirical evidence about the participation role of the different strata of the center manager responsibility in arranging the budget in relation with the procedural justice and managerial performance. Data were collected on a sample of 135 respondents by using a five item questionnaire. A multivariate analysis was carried out. The research findings show a positive correlation and significant between justice procedural and managerial performance through budget participation. It is suggested to the wider research sample by including foreign capital plantation company, domestic capital company, private enterprise, and industry and service company. Keywords: justice procedural - managerial performance - budget participation